Cardiac sarcoidosis in a carrier of transthyretin gene mutation: a case report. Issue 2 (7th February 2023) - Menale, Silvia; Scheggi, Valentina; Vanni, Francesco; Di Mario, Carlo
Abstract: Background: Sarcoidosis is a rare multiorgan inflammatory disorder of unknown aetiology, characterized by the formation of non-caseating granulomas in the affected organs. Cardiac involvement is underrecognized and observed in up to 25% of cases in autopsy studies, and is associated with a high mortality rate, especially due to sudden cardiac death due to ventricular arrhythmias. Case summary: A 41-year-old man well known to our hospital because of his father's diagnosis of cardiac amyloidosis, and carrier of transthyretin ( TTR ) gene mutation, was hospitalized following a resuscitated cardiac arrest. The patient was hospitalized a month before for a syncopal episode with demonstration of preserved left ventricular ejection fraction (LVEF) with akinetic basal septum at heart ultrasound and normal coronary. Chest computed tomography, performed in the emergency department, was significant for hilar lymphadenopathies and pulmonary nodules highly suggestive of sarcoidosis. A subsequent 18-fluorodeoxyglucose-positron emission tomography (FDG-PET) showed multiorgan phlogistic involvement, including the myocardium. After the diagnosis of cardiac sarcoidosis, the patient was started on steroids therapy and underwent ICD implantation. A follow-up 18-FDG-PET showed a reduction of organs glucose uptake and a follow-up echo an improvement in LVEF. Despite that, he occurs occasional recording of repetitive ventricular arrhythmias and one appropriate ICD shock during the next 12 months. Discussion: Cardiac sarcoidosis is an insidious disease. Its diagnosis can be challenging, with no specific finding in echocardiography. The best strategy would be multi-modality imaging involving both magnetic resonance imaging with late gadolinium enhancement and 18-FDG-PET, followed by biopsy to confirm the diagnosis. Multi-modality imaging should be further used to evaluate the response to treatment and assess prognosis. Since the patient was a known carrier of the TTR gene mutation, many efforts were made in order to come up with the correct diagnosis considering that both cardiac amyloidosis and cardiac sarcoidosis are non-ischaemic cardiomyopathy with systemic involvement.